2015
DOI: 10.1134/s102279541506006x
|View full text |Cite
|
Sign up to set email alerts
|

The role of neurotrophins and neurexins genes in the risk of paranoid schizophrenia in Russians and Tatars

Abstract: Schizophrenia affects about 1% of the population. Its etiology is not fully understood. Environ mental conditions certainly contribute to the development of schizophrenia, but the determining factor is genetic predisposition: the coefficient of heritability of schizophrenia is about 80%, which is typical for the most highly heritable multifactorial diseases. Polymorphic loci of genes of enzymes and receptors involved in the processes of neuroprotection and neurotrophia play significant role in the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
(49 reference statements)
0
3
0
2
Order By: Relevance
“…Ama şizofreni hastalarının GAS-6 düzeyleri ile ilgili literatürde herhangi bir çalışmaya rastlanmamıştır. Şizofreninin etyolojisi ile ilgili genetik yatkınlık, çevresel faktörler, otoimmünite, vasküler patolojiler, enflamasyon, enfeksiyon ve stres gibi çok sayıda durumun etkili olduğunu gösteren çalışmalar bulunmaktadır [3,5,6,22,23]. Her ne kadar adı geçen sahalarda çok sayıda araştırma yapılsa da şizofreninin etyopatogenezi tam olarak aydınlatılamamıştır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Ama şizofreni hastalarının GAS-6 düzeyleri ile ilgili literatürde herhangi bir çalışmaya rastlanmamıştır. Şizofreninin etyolojisi ile ilgili genetik yatkınlık, çevresel faktörler, otoimmünite, vasküler patolojiler, enflamasyon, enfeksiyon ve stres gibi çok sayıda durumun etkili olduğunu gösteren çalışmalar bulunmaktadır [3,5,6,22,23]. Her ne kadar adı geçen sahalarda çok sayıda araştırma yapılsa da şizofreninin etyopatogenezi tam olarak aydınlatılamamıştır.…”
Section: Discussionunclassified
“…Farklı klinik tablolar ile kendini gösterebilen kronik seyirli ve tekrarlayıcı bir sendromdur. Genetik, immün aktivite, enfeksiyon, enflamasyon, otoimmün hastalıklar, oksidatif stres, nitrik oksit sistem, vasküler patolojiler ve çevresel faktörler gibi birçok etkenin şizofreni için risk faktörü olduğu iddia edilmektedir [1][2][3][4][5]. Risk faktörleri bu kadar çeşitli olmakla birlikte; altta yatan biyolojik mekanizmanın artmış immün aktivasyon olabileceği düşünülmektedir.…”
Section: Introductionunclassified
“…Thus, it was shown that SNP variant rs6330-A (A35V) (Licinio et al, 2009;Zakharyan et al, 2014), as well as the haplotype rs12760036-C (intr)/rs4839435-A (intr) (in the Korean population) (Park et al, 2011) increase the risk of schizophrenia onset. The variant rs4565713-G (intr) is associated with susceptibility to schizophrenia manifestations in Russian and Tatar populations (Gareeva et al, 2015), and autism in an American population (Chen et al, 2006;Lu et al, 2013). NGF variants rs2856813-G (intr), rs6678788-T (intr), rs4529705-A (intr), rs6537860-A (intr), rs4332358-T (intr), and rs3811014-G (promoter) are associated with primary affective disorders (PAFDs) in women in the American population (Cui et al, 2011).…”
Section: Neurotrophins and Their Receptorsmentioning
confidence: 99%
“…The IBG performed a study in individuals with SZ from the Russian, Tatar, and Bashkir ethnic groups to investigate 88 polymorphisms of 23 candidate genes implicated in neurotransmission and neuronal development. The study found differences in GRIN2B [13], NTRK3 , NXPH1 [14], GRIA2 [15], GRIK2 , RGS2 [16], and TPH1 [17] between SZ patients from the Russian and Tatar ethnic groups. A further study identified risk markers for unipolar depression in SLC6A4 , HTR2A , TPH1 , MAOA , NTRK2 , NTRK3 , NRXN1 , NXPH1 , and MTHFR in both Russians and Tatars [18, 19].…”
Section: The Modern Landscape Of Psychiatric Genetics In the Russian mentioning
confidence: 99%